Leading change through transformational school leadership - Glanz, Jeffrey (Dimensions of leadership and institutional success : exploring connections and partnerships., 2025)
Leading Change through Transformational School Leadership provides insights into the change process as school leaders grapple with many demanding challenges. We are living through tumultuous times, given the unpredictable technological advances, the instability of world politics, the ever-increasing economic disparities worldwide, and the ubiquitous social and cultural upheavals dominating the news through social media. Amidst these global social, political, economic, and cultural transformations, education and schooling remain constants for hope, prosperity, and resilience. Schooling and education have generally been stable institutional and organizational structures, serving students of all ages globally. Schools aren't merely reactive to outside pressures but are, ideally, proactive institutions aiming to forge a better society that provides the requisite knowledge, skills, and ethical dispositions necessary to function in an ever-changing 21st-century milieu. Schools serve to provide high-quality instruction as well as to reinforce common values of goodness, equity, and justice for all. Consequently, schools, although stable forces, must change to meet the challenging needs of 21st-century living. School leaders, in particular, are responsible for creating ways to improve the educational experience. Whether it's adapting the curriculum to meet societal exigencies, creating new programs to support student learning, advancing the education of teachers, providing greater access to parental involvement, forging connections with the surrounding communities, and much more, schools must remain at the forefront of educational change. This book draws from the real world of practice, highlighting attempts to navigate an ever-increasing complex, diverse environment and grappling with internal and external vicissitudes that inevitably challenge a school leader's convictions and intestinal fortitude. Because problems are more intractable today, school leaders have relied on several theories of leadership to guide their work in schools. Transformational school leadership theory provides foundational guidance but also draws from other literature bases concerning teaching, learning, teacher leadership, and systems thinking, for example improvement science, which are formative.